Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Menggambar Bentuk Usia 5-6 Tahun di PAUD Nurul Ikhwan Desa Mondang Kab. Padang Lawas - Wahyuni Wahyuni; Ahmad Syukri Sitorus; Idris Siregar (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research aims to enhance the fine motor skills of children aged 5-6 years through shape drawing activities at PAUD Nurul Ikhwan, Desa Mondang, Kab. Padang Lawas. Fine motor skills, which involve the coordination of small muscle movements, are crucial for activities such as writing and manipulating objects. Despite their importance, these skills are often less emphasized compared to gross motor skills. This study employs Classroom Action Research (CAR) to address observed delays in fine motor development among children at the PAUDNurul Ikhwan.The research consists of two cycles, each incorporating shape drawing activities designed to stimulate and develop fine motor skills. In the initial observation (pratindakan), 11 out of 13 children were identified as having underdeveloped fine motor skills. The first cycle involved introducing drawing activities, but progress was limited. By the second cycle, improvements were noted, with 78% of children achieving satisfactory levels of fine motor development.The findings suggest that regular, engaging drawing activities can significantly enhance fine motor skills in young children. This research underscores the importance of incorporating creative activities like drawing in early childhood education to foster optimal motor development.